2018
DOI: 10.21068/c2018v19n01a13
|View full text |Cite
|
Sign up to set email alerts
|

Diversidad, abundancia relativa y patrones de actividad de los mamíferos medianos y grandes, asociados a los bosques riparios del río Bita, Vichada, Colombia

Abstract: regiones biogeográficas y es poco conocida. Por lo tanto se emplearon técnicas de fototrampeo para el registro de los mamíferos medianos y grandes asociados al bosque ribereño en la cuenca alta y media del río Bita, Vichada, Colombia. Se estimó la diversidad, el índice de abundancia relativa y los patrones de actividad. Se instalaron 77 cámaras trampa a lo largo de 200 km del río en dos periodos hidroclimáticos (baja y alta precipitación). Se obtuvieron en total 16439 imágenes, con un esfuerzo de muestreo de 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
0
7
1
1
Order By: Relevance
“…3), other surveys conducted in these study sites have reported a higher richness than this study. For instance, Pardo & Payán (2015) recorded 16 species in Orocué River (Casanare) and Mosquera-Guerra et al (2018) reported 24 species along the upper and mid basin of the Bita River (Vichada), which is higher than the richness presented here (14 and 9 species, respectively).…”
Section: Se-1 and Se-2contrasting
confidence: 61%
See 2 more Smart Citations
“…3), other surveys conducted in these study sites have reported a higher richness than this study. For instance, Pardo & Payán (2015) recorded 16 species in Orocué River (Casanare) and Mosquera-Guerra et al (2018) reported 24 species along the upper and mid basin of the Bita River (Vichada), which is higher than the richness presented here (14 and 9 species, respectively).…”
Section: Se-1 and Se-2contrasting
confidence: 61%
“…Despite the low anthropogenic transformation of this ecosystem, we found few mammal species, which indicates its vulnerability and makes it a target ecosystem for conservation. However, in SE-3 we did not record other mammals reported for Vichada department such as Tapirus terrestris, Pteronura brasiliensis and Lontra longicaudis (Mosquera-Guerra et al, 2018;Mosquera-Guerra et al, 2017), perhaps because of differences in the sampling design as well as the seasons and vegetation covers that were sampled in each study.…”
Section: Se-1 and Se-2mentioning
confidence: 75%
See 1 more Smart Citation
“…La abundancia hace referencia a la situación poblacional de una especie y su evaluación en distintas escalas (Mosquera et al, 2018). Por otro lado, la diversidad se enfoca en la cifra de especies e individuos, o la abundancia que existe en un medio geográfico.…”
Section: Introductionunclassified
“…In contrast, this region harbors a relatively low level of endemism (Rodríguez-Mahecha et al, 2006;Ferrer et al, 2009). Despite the high biodiversity and studies recently conducted of the region's medium and large mammals (Álvarez & López-Arévalo, 2014;Rodríguez-Bolaños et al, 2015;Olarte-González & Balaguera-Reina, 2015;Mosquera-Guerra et al, 2017;Mosquera-Guerra et al, 2018;Trujillo et al, 2018;Castillo-Figueroa et al, 2019;Pardo et al, 2019), the mammals of the Orinoco River basin are among the least known in Colombia (Hernández et al, 1984;Mosquera-Guerra et al, 2018). The cited studies have a low representatioforest fragmentedn contrast to the size of the Orinoquia and its habitat heterogeneity.…”
Section: Introductionmentioning
confidence: 99%